Voluntary Counseling and Testing untuk Orang Berisiko HIV/AIDS - Diah Astuti Saputri Retnaningsih (al-Balagh : Jurnal Dakwah dan Komunikasi, 2016)
The Study aims to know further about the implementation of Voluntary Counseling and Testing (VCT) to people with the possibility of being infected by HIV/AIDS. It is governmental service program starting from counseling, testing, and post testing in order to minimize the contagious risk of HIV/AIDS. Through the qualitative-descriptive approach, this study showed that the implementation of VCT program is very important because the process emphasizes the acceptance of client, building relationship, exploring, identifying, giving information, planning activity, determining decision, testing, up to developing the readiness of client, making planning, reading off the test’s result, explaining result of the test, giving support and motivation. All of these are purposed to minimize the contagious risk, and make the infected one more optimistic in experiencing life.Keywords: Counseling, Testing, and HIV/AIDS.